Effect of Pharmacist Intervention on Quality of Life of Patients with Major Depressive Disorder in Distressed North East Nigeria (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Quality of life is considered as an integral component and outcome indicator of mental illness and while pharmacist interventions have been proven to be effective in improving quality of life, no attention has been given to patients with depression in distressed North East Nigeria.Objectives: To explore the effect of pharmacist intervention on quality of life of patients with major depressive disorder.Materials and Methods: A longitudinal prospective randomized controlled trial approved by Ahmadu Bello University Ethics Committee on use of Human Subjects for Research (approval number:  ABUCUHSR/2020/018) was conducted on 101 patients with major depressive disorder between April 2019 and March 2020 at a tertiary Neuro-Psychiatric Hospital in Maiduguri, Nigeria. Consenting patients were randomized into Usual Care or Intervention groups using a computer-generated list. The intervention consisted of pharmacist-delivered educational counseling sessions of between 15-30 minutes. Data were collected at baseline, 3 months and 6 months using the World Health Organization Quality of life Bref scale.Results: After the intervention, significant improvements (p